Measuring distortions along Tanzanian agricultural value chains - Majeed, Fahd; Tokgoz, Simla; Allen, Summer L.; Paris, Bas (International Food Policy Research Institute, 2018)
Policies targeting agricultural value chains impact Tanzanian farmers, so it is important to understand how these policies affect producer incentives and price transmission along the value chain. This research focuses on maize and groundnut value chains, estimating Nominal Rates of Protection (NRPs) along the value chain and analyzing their implications for producers. The results for border NRPs and trade status imply an anti-trade bias in maize; imported maize faces an import tariff, while exported maize often faces taxes. Furthermore, maize NRPs at the farmgate are negative, suggesting trade policies are negatively affecting Tanzanian farmers. For the groundnut value chain, border NRPs are consistently negative for all years, regardless of whether Tanzania imports or exports groundnuts and groundnut oil. Farmgate NRPs for groundnuts are negative as well. Groundnut processing and marketing remain undeveloped in Tanzania, and inefficiencies in the groundnut value chain create disincentives for groundnut farmers. For both maize and groundnut value chains, farmgate prices and NRPs for each region show significant variation, indicating the impact of regional/state-level policy framework or other market inefficiencies. Further research on the value chain participants and processing channels is needed to identify opportunities for increasing efficiencies in processing and value addition across these two value chains.